If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -7w + 4x + 8y + 3y + 5w = 0 Reorder the terms: -7w + 5w + 8x + 4x + 8y + 3y = 0 Combine like terms: -7w + 5w = -2w -2w + 8x + 4x + 8y + 3y = 0 Combine like terms: 8x + 4x = 12x -2w + 12x + 8y + 3y = 0 Combine like terms: 8y + 3y = 11y -2w + 12x + 11y = 0 Solving -2w + 12x + 11y = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-12x' to each side of the equation. -2w + 12x + -12x + 11y = 0 + -12x Combine like terms: 12x + -12x = 0 -2w + 0 + 11y = 0 + -12x -2w + 11y = 0 + -12x Remove the zero: -2w + 11y = -12x Add '-11y' to each side of the equation. -2w + 11y + -11y = -12x + -11y Combine like terms: 11y + -11y = 0 -2w + 0 = -12x + -11y -2w = -12x + -11y Divide each side by '-2'. w = 6x + 5.5y Simplifying w = 6x + 5.5y
| -x-17=-4x+1 | | c+18=50 | | -6=2z+14 | | 4x-1+2x=5x+4x | | 1.16x=5.80 | | -y+7=2y+7 | | 35-3v=2v+5 | | 8x+2(-5-3x)=8-7x | | 0=7w-34 | | 6y-42=5y+20 | | b-14=28 | | 6n^2+18n=0 | | 3n+10=91 | | 3(x+3)=14 | | (12m-10)(10m+10)= | | 10x-9y+13=0 | | 4m+2=30 | | 5(8-6x)=-7x+2(-8x-8) | | -0.1x-5x=-18.87 | | 12m-10= | | -x+1=-7x+1 | | a+22=52 | | 5x+26+3x+60=180 | | 4x+2y+0.25z=100 | | 0+y=0 | | 5x+26=3x+60 | | 0.833+2.5x=-6.5+0.66 | | 5x-8y=64 | | 10-4z=22-6z | | 18-3t=6 | | 4(1+2a)=-6a(a-3) | | 5y-3=7y |